Social media for travel tourism and hospitality - Brown, Nancy (Discovery Publishing House, 2023)
Social media is generally considered an information source for travelers, providing electronic word of mouth that allows travelers to obtain information from others with first-hand experience. This view predominates, with social media seen as a type of word-of-mouth communication. This book explores the impact of social media on the tourism industry. It offers a comprehensive overview of the impact of social media on the industry and explores the ways in which organizations can adapt their strategies to stay ahead of the curve.The book covers a broad range of topics, including new service development, marketing, networking, and knowledge management. Providing a combination of theory and practice, drawing on real-life business experiences to analyze the ways in which social media can affect traveler behavior at every stage of the travel process, this book is designed for professionals working in the tourism industry, such as tour developers, travel agents, restaurateurs, and hotel managers. It is also well-suited for entrepreneurs, social media analysts, and industry researchers who are interested in exploring the latest trends and developments in the field.Overall, this book provides valuable insights and practical strategies for anyone involved in the tourism industry.